2013
DOI: 10.1007/s00380-013-0351-0
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent shunt closure after targeted medical therapy can be an effective strategy for secundum atrial septal defect with severe pulmonary arterial hypertension: two case reports

Abstract: Secundum atrial septal defect (ASD) is the most common form of congenital heart disease in adults. Surgical and transcatheter closures of ASD are widely accepted therapeutic approaches. In patients with severe pulmonary arterial hypertension (PAH), however, the closure of the defect is still controversial. We report two cases of ASD patients with severe PAH successfully repaired subsequent to effective medical therapy. Subsequent shunt closure after targeted medical therapy can be an effective strategy in sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Only a few reports have discussed the effects and safety of transcatheter ASD closure for PAH patients who have been treated with recent disease-targeted therapy for PAH. 22- 24 Fujino et al specific medications improved the hemodynamics, and subsequent transcatheter ASD closure was accomplished without any immediate severe complications. Substantial improvement in the WHO-FC was observed with this therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few reports have discussed the effects and safety of transcatheter ASD closure for PAH patients who have been treated with recent disease-targeted therapy for PAH. 22- 24 Fujino et al specific medications improved the hemodynamics, and subsequent transcatheter ASD closure was accomplished without any immediate severe complications. Substantial improvement in the WHO-FC was observed with this therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Successful repair has been demonstrated after treatment with almost all drugs including prostanoids, [28][29][30] PDE5i 31 ERAs [32][33][34] and various drug combinations. [35][36][37] Few authors report PVR, whereas others report PVRI. Operability is decided based on the baseline hemodynamic data by some authors, whereas others perform acute vasodilator testing before deciding operability.…”
Section: Magnitude Of Change In Pvri With Tdtmentioning
confidence: 99%
“…In contrast to the reports discussed above, there are a few patients with ASD and markedly elevated PVRI who have shown unequivocal benefits after TDT and successful clinical outcomes after closure. 32,35,45 Kijima et al showed successful application of ''treat and repair'' approach in their cohort of eight patients who received TDT for a median duration of 2.5 years (range 2 weeks to 10 years). The average PVRI reduced from 14.3 WU.m 2 at baseline to 5.3 WU.m 2 preoperatively.…”
Section: Real Success Storiesmentioning
confidence: 99%
“…However, some case reports or small case series have documented that the shunt closure after PAH therapy was safe and effective in previously inoperable patients [7][8][9].…”
mentioning
confidence: 97%